Statistical and numerical analysis on characteristics and influence factors of construction cracks of large-diameter underwater shield tunnel: a case study - Yang, Rui; Kong, Qian; Ren, Meng; Ji, Fuquan; Li, Dejie (Frontiers in Earth Science, 2023)
Tunnel excavation is prone to segment cracks, which may lead to serious safety accidents. This work aims to investigate the type, location and occurrence time of cracks in a large-diameter underwater shield tunnel and also ascertain the causes of the cracks. The correlations between crack characteristics and shield tunneling parameters were analyzed. The effect of jack deflection and poor assembly on cracks were investigated using a refined finite element model of two consecutive rings with consideration of the assembly clearance and the constraint effect of the shield machine. The results confirmed that 93% of the cracks were formed between the current ring and the last ring jacking stage. Positive cracks induced by jack deflection occurred during the current ring jacking stage, while the lengths of the cracks, proportional to the constraint of the boring machine on the segments, remained constant during the subsequent construction process. The cracks caused by poor assembly quality arose during the current and next ring jacking stages. Furthermore, the cracks generated in the current ring jacking stage would propagate during the subsequent construction process. The type, length, and number of cracks were influenced by the assembly clearance. The inverted V-shape longitudinal joints caused more cracks than any other assembly defects. The finding of this study results and conclusions are expected to contribute to the reduction of cracks at the jacking stage of the large-diameter underwater shield tunnels with eccentricity force transfer platforms.